THE EFFECT OF OBESITY, STRESS AND PROBIOTICS ON THE RESORPTION OF THE ALVEOLAR PROCESS OF THE JAWS IN RATS - V.V. Yevtushok; M.O. Tsebenko; K.S. Neporada (Проблеми екології та медицини)
We studied the role of the probiotic Lactobacillus casei in correcting the resorptive effect on the alveolar process of the jaws in obesity and stress in a model of glutamate-induced obesity and in combination with immobilization stress in rats. We found a reliably significant difference between the groups of intact rats and rats with induced obesity; a group of rats subjected to immobilization stress, and a group of rats with comorbidity of these conditions. The obtained results indicate the resorptive effect of obesity and stress on the bone tissue of the alveolar process of the jaws in animals. At the same time, no statistically significant difference between the groups of rats with obesity, stress, and obesity under stress was found, indicating approximately the same effect of obesity, stress and their combination on the resorption of alveolar bone of the jaws in the studied animals. Analyzing the effectiveness of the probiotic Lactobacillus casei, we found reliable changes between the group of rats in which obesity was modeled and animals with comorbidity of these conditions as compared to the corresponding control. Thus, in the groups of rats, subjected to obesity, and obesity with stress, probiotic correction showed an antiresorptive effect, which is confirmed by a reliably significant difference in the coefficient of exposure of molar roots as compared to the corresponding groups without correction.